The small Rho GTPase Rif and actin cytoskeletal remodelling. (19th January 2012) - Fan, Lifei; Mellor, Harry
Abstract : The Rif GTPase is a recent addition to small Rho GTPase family; it shares low homology with other members in the family and evolutionarily parallels with the development of vertebrates. Rif has the conserved Rho GTPase domain structures and cycles between a GDP-bound inactive form and a GTP-bound active form. In its active form, Rif signals through multiple downstream effectors. In the present review, our aim is to summarize the current information about the Rif effectors and how Rif remodels actin cytoskeleton in many aspects.